Metacognitive Learning Strategies for EFL Autonomous Learning - Damianus Talok; Kletus Erom; Maria Goreti Djehatu; Isabel Coryunitha Panis (Jurnal Komunikasi Pendidikan, 2023)
This study aims to determine whether the research subjects have practiced metacognitive strategies. The method used is qualitative. Eighteen (18) questions are provided, answers to individual questions are written on the guided question sheet in 2 hours - thirty minutes to get the required response. The data proves that planning, monitoring and evaluation is practiced i.e. totaling 100% checks the next day's schedule; (95%) checking what courses to attend; hence they review the previous and upcoming meeting materials. For the next meeting they write notes for questions or to confirm what they don't really understand to the teacher. Likewise, they used process and productive monitoring for 92.5% of what they did before class. Also, the data shows that they evaluate; 95% evaluated after class.